2021
DOI: 10.1159/000514311
|View full text |Cite
|
Sign up to set email alerts
|

MiR-22-3p Suppresses Vascular Remodeling and Oxidative Stress by Targeting CHD9 during the Development of Hypertension

Abstract: Hypertension is considered a risk factor for a series of systematic diseases. Known factors including genetic predisposition, age, and diet habits are strongly associated with the initiation of hypertension. The current study aimed to investigate the role of miR-22-3p in hypertension. In this study, we discovered that the miR-22-3p level was significantly decreased in the thoracic aortic vascular tissues and aortic smooth muscle cells (ASMCs) of spontaneously hypertensive rats. Functionally, the overexpression… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 53 publications
1
7
0
Order By: Relevance
“…Similarly, Fu et al observed that miR-22-3p down-regulation facilitated the proliferative and migrating properties of VSMCs in atherosclerosis. 21) In addition, the research of Chen et al unraveled that miR-22-3p overexpression caused the transformation of aortic SMCs from the synthetic to contractile phenotype, 22) which was concurrent with our finding. Moreover, it was documented that the dysregulation of ECs is another mechanism implicated in ISR in addition to ECM deposition, aberrant proliferation, phenotype transformation, and migration of VSMCs.…”
Section: Discussionsupporting
confidence: 90%
“…Similarly, Fu et al observed that miR-22-3p down-regulation facilitated the proliferative and migrating properties of VSMCs in atherosclerosis. 21) In addition, the research of Chen et al unraveled that miR-22-3p overexpression caused the transformation of aortic SMCs from the synthetic to contractile phenotype, 22) which was concurrent with our finding. Moreover, it was documented that the dysregulation of ECs is another mechanism implicated in ISR in addition to ECM deposition, aberrant proliferation, phenotype transformation, and migration of VSMCs.…”
Section: Discussionsupporting
confidence: 90%
“…These results indicated that holding miR‐22‐3p at the physiological level was required for maintaining oxidative balance. Interestingly, a previous study demonstrated that miR‐22‐3p was responsible for suppressing oxidative stress in aortic vascular cells of SHRs (Chen et al., 2021). The probable reason for these two conflicting results may be attributed to a downstream target difference.…”
Section: Discussionmentioning
confidence: 99%
“…A previous study found that LMNA (lamin A/C) [85], SLC11A2 [163], CRTC2 [164], TBK1 [165], GRN (granulin precursor) [166], CTSD (cathepsin D) [167], STARD10 [168], PGRMC1 [169], TFE3 [170], POR (cytochrome p450 oxidoreductase) [171], SESN1 [172], IL15 [173], PIK3R1 [134], OSM (oncostatin M) [98], SOCS3 [174], USP21 [100], GLUL (glutamate-ammonia ligase) [175], IL1R1 [176], TP53 [177], PPM1A [178], CTBP1 [179], DNAJC3 [180], ATP6 [181], DDX21 [182], COX2 [183], RACK1 [184], ND1 [158], CCND2 [185] and COX1 [186] are positively correlated with type 2 diabetes mellitus, suggesting its potential as a biomarker for type 2 diabetes mellitus. LMNA (lamin A/C) [187], PFKFB3 [188], TRAF2 [189], ADORA2B [190], ACADS (acyl-CoA dehydrogenase short chain) [191], IRF7 [192], ASL (argininosuccinatelyase) [193], IL15 [194], PIK3R1 [195], OSM (oncostatin M) [196], SOCS3 [197], CHD9 [198], IFI44L [199], GNLY (granulysin) [200], FLNB (filamin B) [201], IL1R1 [202], SETD3 [203], TP53 [204], BRD4 [205], COX2 [206], HSP90AB1 [207], SLC7A1 [208], ND2 [209] and COX1 [210] have been reported to be associated with hypertension. LMNA (lamin A/C) [211], INPP5K [212], SCYL1 [213], AKR7A2 [214], TRAF2 [215], SLC11A2 [216], NEU1 [217], SNAP29 [218], DUSP22 [219], P2RX4 [220], ADORA2B [221], NAXD (NAD(P)HX dehydratase) [222], FEZ1 [223], TBK1 [224], GRN (granulin precursor) [225], ATG4D [226], CTSD (cathepsin D) [227], PPP2R5D […”
Section: Discussionmentioning
confidence: 99%